2007
DOI: 10.2527/jas.2006-434
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and intestinal morphology responses in early weaned pigs to supplementation of antibiotic-free diets with an organic copper complex and spray-dried plasma protein in sanitary and nonsanitary environments1

Abstract: The objective of this study was to determine the effects of addition of spray-dried plasma protein (SDPP) and Cu to nonmedicated diets on growth performance and intestinal morphology in weaned pigs reared in sanitary or nonsanitary environments. Weanling pigs (n = 192, 18 +/- 2 d of age, 6.0 +/- 0.2 kg of BW) were assigned to 8 treatments arranged factorially, including 2 dietary levels of SDPP (0 or 6% for the initial 10 d), 2 levels of added dietary Cu (0 or 200 ppm for the entire 35-d experiment), and 2 pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 35 publications
3
66
1
Order By: Relevance
“…Armstrong et al (2004) showed that lower dietary Cu concentrations (125 ppm from either Cu citrate or CuSO 4 ) were as effective as 250 ppm of Cu from CuSO 4 at stimulating the growth of weanling pigs over a 45-d nursery period. Zhao et al (2007) found that 200 ppm Cu from a commercial Cu proteinate complex is an effective growth promoter in pig the first 10 days of the post-weaning period, but has no effect if considered during the overall post-weaning period (35 days) of dietary treatment. Smith et al (1997) found that 28-d growth performance of weaning pig fed 250 ppm Cu from CuSO 4 on a commercial farm did not differ from that of controls.…”
Section: Discussionmentioning
confidence: 98%
“…Armstrong et al (2004) showed that lower dietary Cu concentrations (125 ppm from either Cu citrate or CuSO 4 ) were as effective as 250 ppm of Cu from CuSO 4 at stimulating the growth of weanling pigs over a 45-d nursery period. Zhao et al (2007) found that 200 ppm Cu from a commercial Cu proteinate complex is an effective growth promoter in pig the first 10 days of the post-weaning period, but has no effect if considered during the overall post-weaning period (35 days) of dietary treatment. Smith et al (1997) found that 28-d growth performance of weaning pig fed 250 ppm Cu from CuSO 4 on a commercial farm did not differ from that of controls.…”
Section: Discussionmentioning
confidence: 98%
“…The availability of both protein sources is substantial and may provide a new alternative supplement for animal feeds or for functional foods for humans [25,26]. The beneficial effects on growth performance resulting from the inclusion of SDAP-containing IgG in diets for early weaned animals have been reported in various studies [6,7,10,14,27,28]. Among plasma proteins, albumin is the most abundant, normally comprising 50-70% of total protein and the other three abundant proteins are the alpha, beta, and gamma globulins.…”
Section: Discussionmentioning
confidence: 99%
“…animals such as pigs, calves, broilers, and turkeys [1][2][3][4][5][6][7]. These effects are more pronounced when animals are challenged with pathogenic bacteria or toxins [1,[8][9][10][11][12].…”
mentioning
confidence: 99%
“…Increased villus/crypt ratio equates to more absorptive area. Many authors have reported villus atrophy after weaning and fasting (Pluske et al, 1997;Tang et al, 1999;Ferraris and Carey, 2000) but SI mucosal architecture has been shown to be affected also by weaning age (Gu et al, 2002), type of diet and route of its administration (Li et al, 1991;Zijlstra et al, 1996;Niinikoski et al, 2004), type of colonizing commensal bacteria and pen sanitation conditions (Zhao et al, 2007).…”
Section: Intestinal and Mucosal Mass And Functional Morphologymentioning
confidence: 99%